Anthropology 08/09 : Annual Editions - Elvio Angeloni (The Mc Graw-Hill Companies, 2008)
Anthropology 08/09 is one in a series of over sixty-five volumes, each designed to provide convenient, inexpensive acces to a wide range of current, carefully selected articles from some of the most respected magazine, newspapers, and journals published today.